Associations between demographic characteristics and resilience factors: A self-report survey - Mohamed Ludin, Salizar (IIUM Press, 2018)
Objective: In 2014, Malaysia suffered a severe flood disaster and many people lost their home and belongings. Despite regular flooding in this area, the status of community disaster resilience (CDR) is unknown. This paper thus aims to assess the association between demographic characteristics and community disaster resilience factors. Methods: A cross-sectional study was completed using the Conjoint Community Resiliency Assessment Measure (CCRAM28) questionnaire six months after the flood event occurred. All selected respondents who met the inclusion criteria were recruited, and IBM SPSS software was used to undertake descriptive and inferential analysis. Results: A total of 386 respondents completed the questionnaires. Respondents were mostly female (57%); married (83.9%); with children under 17 years old (58.8%); from villages or rural area (97.2%); living in basic housing (95.6%); of average income; Muslim (97.5%); educated to primary or secondary level (81.1%); and not involved with any community organizations (95.1%), including volunteering, emergency teams, or military service. The mean age was 49 years, and length of time living in the area ranged from 1 to 85 years. CDR scores ranged between medium (2.34- 3.66) and high (3.67- 5.00). An analysis of the results showed that only gender (p = 0.003) and education (p = 0.001) were significantly related to CDR level. Positive and strong correlations were seen between resilience factors, however, particularly leadership (p = 0.001), collective efficacy (p = 0.001); preparedness (p = 0.001); place attachment (p = 0.001); and social trust (p = 0.001). Conclusion: The study provides a timely insight into the impact of demographic characteristics and resilience factors in Kelantan, developing the knowledge base needed to create comprehensive, improved community-relevant strategies for the future. This assessment enables top-down initiatives to better understand resilience levels, and this could act as tool to enable the government to prepare communities for future disasters or emergency events.